Pacing strategy determinants during a 10-km running time trial: Contributions of perceived effort, physiological, and muscular parameters. - Bertuzzi, R.; Lima-Silva, A. E.; Pires, F. O.; Damasceno, M. V.; Bueno, S.; Pasqua, L. A.; Bishop, D. J. (The Journal of Strength and Conditioning Research, 2014)
The purpose of this study was to identify the main determinants of the self-selected pacing strategy during a 10-km running time trial. Twenty eight male long-distance runners performed the following tests: (a) maximal incremental treadmill test, (b) economy running test, (c) maximum dynamic strength test, and (d) 10-km running time trial on an outdoor track. A stepwise multiple regression model was used to identify the contribution of rating of perceived exertion (RPE), physiological, and muscular parameters on the pacing strategy adopted by athletes. In the start phase (first 400 m), RPE accounted for 72% (p = 0.001) of the pacing variance. Peak treadmill speed (PTS) measured during a maximal incremental test explained 52% (p = 0.001) of the pacing variance during the middle phase (400-9,600 m), whereas maximal oxygen uptake and maximum dynamic strength accounted for additional 23% (p = 0.002) and 5% (p = 0.003), respectively. In the end phase (last 400 m), PTS accounted alone for 66% (p = 0.003) of the pacing variance. These data suggest that predictors of the pacing strategy during a 10-km running time trial have a transitional behavior from perceptive (start phase) to muscular and physiological factors (middle and end phases).